Triple water clear cell parathyroid adenomas: a rare cause of primary hyperparathyroidism. Issue 4 (12th April 2022) - Parpounas, Constantinos; Lyssiotis, Theodoros; Constantinides, Vasilis
Abstract : A man in his 70s was referred to the endocrine surgery department after incidental finding of hypercalcaemia during preoperative work-up for abdominal aortic aneurysm repair. The patient reported severe fatigue and malaise with no previous history of nephrolithiasis or osteoporosis. After biochemical confirmation of primary hyperparathyroidism, localisation studies suggested multiple gland disease. Intraoperatively, three enlarged parathyroid adenomas were found and excised. Histopathological and immunohistochemical examination revealed triple water clear cell (WCC) parathyroid adenomas. Adenomas being entirely composed of WCCs are rare. In addition, triple adenomas are so rare that their existence is disputed by some authors. The present paper reports on an extremely rare case of a patient suffering from triple parathyroid adenomas composed entirely of WCCs. To our knowledge, this is the first such reported case in the English language literature.